Hibiscus sabdariffa anthocyan stabilization tests by co-maceration of crushed calices with powder of Saba senegalensis fruit bark and combretum Micranthum leaf - Faye, Papa Guedel; Niane, Khadim; Niang, Lahat; Balde, Samba; Cisse, Oumar Ibn Khatab; Sow, Alioune; Ayessou, Nicolas Cyrille; Cisse, Mady (International Journal of Chemical and Process Engineering Research, 2023)
Tannins can interact with anthocyanins to form complexes that stabilize color and protect anthocyanins from degradation. Thus, this work proposes to study the effect of the tannins of bark of the fruit of Saba Senegalensis and Combretum Micranthum on the stability of the anthocyanins of drink based on red calyxes of hibiscus obtained by co-maceration. The anthocyanin concentration was determined by the pH-differential method. The red color degradation index is determined based on the CIELAB (International Commission of Lighting) color system (L*, a*, b* and L*). R and Minitab 18 software were used for data processing. Monitoring of the residual anthocyanin content and the intensity of the red color was carried out over eight weeks. The results showed that Saba Senegalensis tannins interact better with anthocyanins. After eight weeks of storage at 4°C, 89.36 % of the anthocyanins are preserved with the Saba S tannins against 83.62 % for the control batches and 80.38 % for the Combretum tannins. Storage at 37°C for eight weeks reveals very high loss rates, 14.86 % of the anthocyanins are preserved (Saba tannins) against 3.38 % for the control and 1.84 % with the Combretum tannins. Moreover, the intensity of the red color is better preserved at 4 °C and 37 °C with the tannins of Saba Senegalensis.